EP251 Cervical cancer in HIV-seropositive women. (1st November 2019) - Assal, A; Moukhliss, S; Benchrifi, Y; Benhessou, M; Ennachit, M; El Karroumi, M
Abstract : Introduction/Background: The aim of our work is to study the epidemiological, clinical, and therapeutic characteristics of cervical cancer in HIV-positive patients under antiretroviral therapy. Methodology: This is a retrospective study of 13 years extending from 2003 to 2016 in the department of infectious diseases at CHU Ibn Rochd of Casablanca. Were included all patients infected with HIV and presenting a cervical cancer histologically documented. Data were collected from electronic records (Nadis software). Results: We included 16 cases of invasive cervical cancer. The median age was 41, 1 years. The concepts of recurrent STIs and active smoking were found in all patients. Cervical cancer has occurred to the waning of therapeutic followed in the majority of cases. At the time of cancer diagnosis, all patients were immunohierological success. This was squamous cell carcinoma in 7 cases, 4 had stage IIIB and 3 cases in stage II Bd. Five patients were treated with radiotherapy alone. Five patients died by peritoneal carcinomatosis with liver metastasis. Conclusion: Cervical cancer screening must be systematic for any woman infected with HIV. The rythm of screening should be annual, and the availability and accessibility of screening can have a positive impact on reducing the prevalence and progression of precancerous cervical lesions by providing early access to appropriate care. Disclosure: Nothing to disclose.